2021
DOI: 10.31729/jnma.6501
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Thyroid Hormone among Patients with Ischemic Stroke visiting a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Stroke is broadly classified as cerebral infarction, intracerebral hemorrhage and subarachnoid hemorrhage. Neuroendocrine profile is altered in acute ischemic stroke and there is a link between hypothyroidism and atherosclerosis which in turn may lead to stroke. The objective of this study was to find out the prevalence of alteration of thyroid hormones in patients with ischemic stroke in a tertiary care center. Methods: This descriptive cross-sectional study was conducted from June to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To date, clinical studies on alterations of THs levels and stroke have focused mainly on the correlation between the low T3 syndrome and a worsened clinical outcome. In acute stroke patients, the incidence of low T3 levels varied from 15.1% [ 94 ] to 37% [ 73 ]. These studies have demonstrated the association between lower T3 levels with greater stroke severity [ 74 , 95 ], infections [ 96 ], more complicated in-hospital clinical course [ 95 ], greater mortality rates [ 74 , 95 ] and a higher risk of poor functional outcome [ 73 , 74 , 76 , 77 , 95 , 97 , 98 ].…”
Section: Thyroid Hormones and Clinical Outcomes In Post-stroke Patientsmentioning
confidence: 99%
“…To date, clinical studies on alterations of THs levels and stroke have focused mainly on the correlation between the low T3 syndrome and a worsened clinical outcome. In acute stroke patients, the incidence of low T3 levels varied from 15.1% [ 94 ] to 37% [ 73 ]. These studies have demonstrated the association between lower T3 levels with greater stroke severity [ 74 , 95 ], infections [ 96 ], more complicated in-hospital clinical course [ 95 ], greater mortality rates [ 74 , 95 ] and a higher risk of poor functional outcome [ 73 , 74 , 76 , 77 , 95 , 97 , 98 ].…”
Section: Thyroid Hormones and Clinical Outcomes In Post-stroke Patientsmentioning
confidence: 99%
“…Stroke could cause changes in thyroid function in nonthyroidal illness, at least in the acute phase (Theodoropoulou et al., 2006 ). A cross‐sectional study revealed that the prevalence of thyroid hormone alterations among acute ischemic stroke patients without known thyroid diseases was 17.8% (13/73) (Bashyal et al., 2021 ). Low T3 syndrome is characterized by low free T3 (FT3) level together with normal‐to‐low free T4 (FT4) and TSH levels (Gao et al., 2018 ), and it is reported that low T3 syndrome affects 32%–62% of patients undergoing acute cerebrovascular diseases (Bunevicius et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%